A review on various methods for dehazing images - Ahmed Rafid Hashim 1* Hazim G. Daway 2 Hana H. kareem3 ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
In this paper, a literature survey was introduced to study of enhancing  the hazy images   , because most of the images captured in outdoor images have low contrast, color distortion, and limited visual because the weather conditions such as haze and that leads to decrease the quality of images capture. This study is of great importance in many applications such as surveillance, detection, remote sensing, aerial image, recognition, radar, etc. The published researches on haze removal are divided into several divisions, some of which depend on enhancement the image, some of which depend on the physical model of deformation, and some of them depend on the number of images used and are divided into single-image and multiple images dehazing model , therefore, the haze and its model were studied and the research and methods that dealt with the removal of haze were explained and detailed its advantage and disadvantage which is required for further study.